2017
DOI: 10.1016/j.marpolbul.2016.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the long-term evolution of worst-case Arctic oil spills

Abstract: We present worst-case assessments of contamination in sea ice and surface waters resulting from hypothetical well blowout oil spills at ten sites in the Arctic Ocean basin. Spill extents are estimated by considering Eulerian passive tracers in the surface ocean of the MITgcm (a hydrostatic, coupled ice-ocean model). Oil in sea ice, and contamination resulting from melting of oiled ice, is tracked using an offline Lagrangian scheme. Spills are initialized on November 1st 1980-2010 and tracked for one year. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Ice also rafts pollutants such as polychlorinated biphenyls, pesticides, heavy metals, and microplastics (Newton et al, 2017;Peeken et al, 2018;Pfirman et al, 1995Pfirman et al, , 2009. Thousands of square kilometers of ice arrive annually from Alaskan or Russian waters, where companies such as Rosneft, Gasprom, PAO Novatek, Royal Dutch Shell, and Chevron hold exploration and development leases, representing potentially disastrous sources of pollutant releases into the ice pack (Blanken et al, 2017;National Research Council, 2014;Newton et al, 2017;Rosen, 2020). To protect sea-ice habitats in the LIA requires, therefore, scientifically sound stewardship of ice sources and pathways, what we refer to as the LIA's ice shed (Pfirman et al, 2009), in addition to managing development within the LIA itself.…”
Section: Protecting the Lia Means Protecting The Ice Source Regionsmentioning
confidence: 99%
“…Ice also rafts pollutants such as polychlorinated biphenyls, pesticides, heavy metals, and microplastics (Newton et al, 2017;Peeken et al, 2018;Pfirman et al, 1995Pfirman et al, , 2009. Thousands of square kilometers of ice arrive annually from Alaskan or Russian waters, where companies such as Rosneft, Gasprom, PAO Novatek, Royal Dutch Shell, and Chevron hold exploration and development leases, representing potentially disastrous sources of pollutant releases into the ice pack (Blanken et al, 2017;National Research Council, 2014;Newton et al, 2017;Rosen, 2020). To protect sea-ice habitats in the LIA requires, therefore, scientifically sound stewardship of ice sources and pathways, what we refer to as the LIA's ice shed (Pfirman et al, 2009), in addition to managing development within the LIA itself.…”
Section: Protecting the Lia Means Protecting The Ice Source Regionsmentioning
confidence: 99%
“…A useful method to study sea ice drift pattern is by using passive microwave satellite images combined with the motions of sea ice buoys 16 , 17 , which highlight the role of sea ice, e.g. spreading oil spills 18 . Recent studies stress the changes caused by the shift to first year ice resulting in the tendency of sea ice floes to diverge from the main drift pattern 19 such as the Transpolar Drift, with complex effects on exchange processes of any contaminants between the exclusive economic zones (EEZ) of the various Arctic nations 20 .…”
Section: Introductionmentioning
confidence: 99%
“…), the extreme cold, seasonal darkness, remoteness, and presence of sea 10.1002/2016EF000500 ice will make containment and recovery extremely difficult, if not impossible [Sørstrøm et al, 2010;Harvey and Walker, 2013]. Blanken et al [2017], for example, found that sea ice will transport oil (and presumably other contaminants) significantly farther than ocean currents. The US National Academies of Science has recently completed a major study of the state of oil-spill management in the Arctic [National Academies of Science (NAS), 2014], and industry groups are investing in studies and experiments to develop response strategies [Sørstrøm et al, 2010].…”
Section: Introductionmentioning
confidence: 99%